Effective Strategies for Human Resource Development in the Digital Era - Sanjayyana, Adzka Rosa; Sutarsa, Monika; Romdoni, Nijar Kurnia; Fitriani, Rani Ligar (PT. Riset Press International, 2024)
The rapid development of digital technology has brought significant changes in various aspects of life, including the field of human resource management (HR). This article aims to identify and analyze effective strategies that can be applied in human resource development in the digital era. In this context, HR development strategies do not only focus on improving technical skills, but also on developing soft skills which are essential for adaptation in a dynamic work environment. This research uses a qualitative approach with a comprehensive literature study method, reviewing various academic and practical sources. relevant to the topic. The main findings of this study show that the integration of technology in the training and development process, the formation of a work culture that supports innovation, and the implementation of a digital-based performance management system are some of the key effective strategies. Apart from that, the importance of visionary and adaptive leadership has also been identified as a determining factor for success in HR development in the digital era. This article provides insight for HR practitioners and managers to formulate HR development policies and programs that are relevant to the demands of the times. In addition, this research also makes a theoretical contribution by offering a conceptual framework for holistic and sustainable human resource development in the digital era.